Experimental intraocular infection of Japanese quails (Coturnix coturnix japonica) with Infection Bursal Disease Virus (IBDV) intermediate strain - Mahamud, Siti Nor Azizah (2016)
Infectious Bursal Disease (IBD) was first discovered in 1957 at Gumboro, Delaware, USA and was first described in Malaysia in 1991. IBD became an important viral disease in poultry industry due to its significant economic losses with high mortality and profound immunosuppression. This experiment was conducted to induce the Japanese quails with IBD modified-live vaccine intermediate strain intraocularly. The parameters obtained were observation of clinical signs, post-mortem lesions, antigen detection using conventional reverse transcriptase PCR and histopathological changes in quails from group A, B and C respectively. Specific primer was designed to target the major outer capsid protein which is viral protein 2 gene (VP2). These parameters are measured after vaccine administration and selected number of quails from each group were euthanized at day 5, 9 and 15 post-infection and the total of 24 bursas were collected. The result reveals minor lymphoid depletion in Group A, prominent clinical signs and mild lymphoid depletion for Group B and no significant post-mortem findings in all groups. RT-PCR analysis gave negative findings in all samples tested. In conclusion, clinical, pathological and molecular results indicate that IBDV intermediate strain does not produce sufficient immune respond in quails to warrant them as carrier or host.